2012
DOI: 10.5194/cp-8-995-2012
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the North Atlantic climate to Greenland Ice Sheet melting during the Last Interglacial

Abstract: Abstract.During the Last Interglacial (LIG;∼130 000 yr BP), part of the Greenland Ice Sheet (GIS) melted due to a warmer than present-day climate. However, the impact of this melting on the LIG climate in the North Atlantic region is relatively unknown. Using the LOVE-CLIM Earth system model of intermediate complexity, we have systematically tested the sensitivity of the LIG climate to increased freshwater runoff from the GIS. In addition, experiments have been performed to investigate the impact of an idealiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 69 publications
1
19
1
Order By: Relevance
“…Govin et al (2012) considered the melting of the Greenland ice sheet and its influence on surface temperatures and NADW formation at 126 ka and showed a slowdown of the AMOC along with reduced SSTs in the North Atlantic, but the timing of the cooling from the new data synthesis of Capron et al (2014) predates conditions at 126 ka. Similar work by Bakker et al (2012) and OttoBliesner et al (2006) showed that melting of the Greenland ice sheet resulted in a reduction in the AMOC strength and cooling in the vicinity of the Labrador Sea. Goelzer et Figure 2.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…Govin et al (2012) considered the melting of the Greenland ice sheet and its influence on surface temperatures and NADW formation at 126 ka and showed a slowdown of the AMOC along with reduced SSTs in the North Atlantic, but the timing of the cooling from the new data synthesis of Capron et al (2014) predates conditions at 126 ka. Similar work by Bakker et al (2012) and OttoBliesner et al (2006) showed that melting of the Greenland ice sheet resulted in a reduction in the AMOC strength and cooling in the vicinity of the Labrador Sea. Goelzer et Figure 2.…”
Section: Introductionmentioning
confidence: 48%
“…As a result of this range in response of AMOC collapse to freshwater input, we perform an analysis of the response of the high-latitude regions to varying amounts of freshwater forcing in the North Atlantic to test the sensitivity of the model under 130 ka forcing conditions. This is similar to the study of Bakker et al (2012), which looked at the sensitivity of the AMOC to Greenland ice-sheet melt during the LIG using a climate model of intermediate complexity. Figure 9 shows the model summer North Atlantic temperature response (averaged over the locations for which Capron et al, 2014, provide temperature records) for freshwater input, varying from 0 to 1 Sv compared with the average NH temperature anomaly from the Capron et al (2014) dataset (horizontal dashed line).…”
Section: Resultsmentioning
confidence: 73%
“…Several transient modelling experiments and proxy-based temperature reconstructions for both the present interglacial (PIG) and the LIG have shown that there are large regional differences in the timing of interglacial maximum warmth, of the order of several thousands of years (Renssen et al, 2009Bakker et al, 2012;Govin et al, 2012;Langebroek and Nisancioglu, 2014). These temporal differences result from latitudinal and seasonal differences in the evolution of the orbital forcing, from the thermal inertia of the oceans and from a variety of feedbacks in the climate system, such as the presence of remnant ice sheets from the preceding deglaciation, changes in sea-ice cover, vegetation, meridional overturning strength and monsoon dynamics.…”
Section: P Bakker and H Renssen: Last Interglacial Model-data Mismatchmentioning
confidence: 99%
“…The last interglacial period (LIG; ∼ 130-116 thousand years before present [ka]) receives increasing attention because of the potential to constrain the impact of climate feedbacks such as increased melt rates of the major ice sheets in warm climates (Otto-Bliesner et al, 2006;Bakker et al, 2012Bakker et al, , 2013Stone et al, 2013) and to evaluate climate model performance for a warmer than present-day climate (Otto-Bliesner et al, 2006Lunt et al, 2013;MassonDelmotte et al, 2013). To facilitate the model-data comparisons that are crucial in the evaluation of climate model performance, a number of compilations of reconstructed maximum LIG temperatures have been produced (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…sum of excess precipitation and snow melt), which is then evenly distributed over 10 major runoff points (c.f. Bakker et al, 2012) for locations of river outflow points.…”
Section: Snapshot Experimentsmentioning
confidence: 99%